Menalar Konstruksi Sejarah Pembentukan Madzhab Fiqh Islam dalam Upaya Menyelaraskan Moderasi Bermadzhab - Murdan, Muhammad Nur (Al Mabhats : Jurnal Penelitian Sosial Agama, 2022)
Abstract: The development of Islamic law (sharia) must be connected to the situation and conditions of the society it faces. This phenomenon has been evident since the prophetic era and continued to develop after the passing of Prophet Muhammad, where the application and establishment of several Islamic laws were formulated through the method of ijtihad (consensus and analogy). The results of ijtihad were then followed by ordinary Muslims, forming certain groups and factions who believed in the truthfulness of their mujtahid imams. At the grassroots level, these differences escalated into disputes and factional fanaticism, sometimes resulting in phenomena within the Muslim community. This article attempts to revisit the history of forming fiqh (Islamic law) schools to strengthen and align moderation in being affiliated with a specific school of thought amid the rigidity of the Muslim community, who blamed each other between schools of thought and another. Abstrak: Perkembangan syariat Islam tidak lepas dari situasi dan kondisi masyarakat yang dihadapinya. Hal ini terlihat sejak era kenabian dan selanjutnya berkembang pada masa sepeninggal Nabi Muhammad saw., dimana penerapan dan penetapan beberapa hukum Islam dirumuskan dengan metode ijtihad (ijma’ dan qiyas). Hasil ijtihad tersebut selanjutnya diikuti oleh ummat Islam yang awam, membentuk kelompok dan golongan tertentu, yang saling meyakini kebenaran imam mujtahid mereka. Perbedaan-perbedaan itu, pada tatanan masyarakat bawah meruncing menjadi perselisihan dan fanatisme golongan, sehingga terkadang masyarakat dihadapkan pada fenomena dalam intern Islam. Tulisan ini mencoba mengulas kembali sejarah pembentukan madzhab fiqh (hukum Islam) dalam usaha menguatkan dan menyelaraskan moderasi dalam bermadzhab di tengah-tengah kejumudan ummat yang saling menyalahkan antara satu madzhab dengan madzhab yang lainnya.